1998
DOI: 10.1046/j.1523-1755.1998.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of human uropontin to inhibition of calcium oxalate crystallization

Abstract: Uropontin (UP) is known to inhibit the growth and nucleation of calcium oxalate monohydrate (COM) crystals, and it also impedes attachment of calcium oxalate crystals to cultured renal epithelial cells. However, its role in normal defense against renal crystallization, and in pathogenesis of nephrolithiasis is unclear. In this study we determined the effect of UP on aggregation of COM crystals as well as the inhibitory activity of UP on COM crystal growth and nucleation in a series of normal subjects, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 18 publications
3
86
0
1
Order By: Relevance
“…(40) We have reported evidence of OPN as a promoter of kidney stone formation (5)(6)(7)(8)(9) ; however, opposing opinions suggest that OPN is an inhibitor. (10)(11)(12) This controversy has not been resolved, but knowledge of stone elimination (13)(14)(15) indicates two possible functions of OPN during kidney stone formation-as a promoter of early crystal conversion to stones and as an inhibitor of kidney stone formation, acting as an opsonin-like molecule involved in crystal digestion by macrophages. Investigation of the crystal elimination process using OPN knockout mice should be continued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) We have reported evidence of OPN as a promoter of kidney stone formation (5)(6)(7)(8)(9) ; however, opposing opinions suggest that OPN is an inhibitor. (10)(11)(12) This controversy has not been resolved, but knowledge of stone elimination (13)(14)(15) indicates two possible functions of OPN during kidney stone formation-as a promoter of early crystal conversion to stones and as an inhibitor of kidney stone formation, acting as an opsonin-like molecule involved in crystal digestion by macrophages. Investigation of the crystal elimination process using OPN knockout mice should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using two types of transgenic mice with conversion of the Arg-Gly-Asp (RGD) sequence, the cell-attachment domain of OPN, to the Arg-Gly-Glu (RGE) sequence and lack of two calcium-binding sites consisting of an aspartate chain, we found that each domain could affect the number of kidney CaOx crystals and crystal morphology, respectively, and confirmed OPN function in kidney stone formation as a promoter. (9) However, other reports have demonstrated OPN as an inhibitor of kidney stone formation, (10)(11)(12) although there also have been many studies about the influence of expression change or singlenucleotide polymorphisms (SNPs) of many genes that are related to other stone matrix proteins, urinary high-molecular-weight substances, extracellular matrix, chemotaxis, oxidative stress, cell adhesion, immune reactions, coagulation, oncogene, cell injury, oxalate and calcium metabolism, tubular transporter, lipid metabolism, and so forth. To advance investigations of the genetic background of kidney stone formation, we established a stone-formation mouse model that could become a base of gene recombinant animals (13) and discovered a new phenomenon, stone elimination, during the experimental process.…”
Section: Introductionmentioning
confidence: 99%
“…In normal kidneys, OPN is secreted by the thin and thick ascending limbs of the loop of Henle and distal nephrons (27)(28)(29)(30)(31)(32). OPN contains a 15-20% aspartic acid residue content, and the mineral binding and inhibitory properties of OPN have often been partly attributed to an aspartic acidrich sequence within this protein (10,26,33,34).…”
mentioning
confidence: 99%
“…OPN consistently localizes to kidney stones (37) and at physiologically relevant concentrations applied in vitro, acts as a potent inhibitor of the nucleation, growth, and aggregation of calcium oxalate crystals (27,30,34). In a rat model of urolithiasis, although increased OPN mRNA expression was associated with increased renal calculi formation, the urinary excretion level of OPN was less than in controls, discussed as being attributable to incorporation of OPN into stones (37,38).…”
mentioning
confidence: 99%
“…Calculi contains some proteins normally present in urine, in addition to others arising from injury inflicted by the stones themselves, making it impossible to discriminate between those that bind to the stone as it grows, but play no role in its development (7); the inhibition is generally understood to arise mainly from the non-dialyzable molecules of urine, particularly acid glycoproteins, and acidic glycoproteins and glycosaminoglycans (8,9). Some inhibitor molecules have been identified, including Tamm-Horsefall Protein, uropontin (10,11), calgranulin (12), bikunin (13), and prothrombin F1 fragment (14). Thus, in order to understand the mechanism of stone genesis, it is essential to determine the characteristics of molecules constituting the urinary stone matrix.…”
Section: Introductionmentioning
confidence: 99%